Differential changes in self-reported aspects of interoceptive awareness through 3 months of contemplative training - Bornemann, Boris; Herbert, Beate M.; Mehling, Wolf E.; Singer, Tania (Frontiers in Psychology, 2015)
Interoceptive body awareness (IA) is crucial for psychological well-being and plays an important role in many contemplative traditions. However, until recently, standardized self-report measures of IA were scarce, not comprehensive, and the effects of interoceptive training on such measures were largely unknown. The Multidimensional Assessment of Interoceptive Awareness (MAIA) Questionnaire measures IA with 8 different scales. In the current study, we investigated whether and how these different aspects of IA are influenced by a 3-month contemplative intervention, in the context of the ReSource project, in which 148 subjects engaged in daily practices of “Body Scan” and “Breath Meditation”. We developed a German version of the MAIA and tested it in a large and diverse sample (n=1,076). Internal consistencies were similar to the English version (.56-.89), re-test reliability was high (rs: .66-.79), and the MAIA showed good convergent and discriminant validity. Importantly, interoceptive training improved 5 out of 8 aspects of IA, compared to a retest control group. Participants with low IA scores at baseline showed the biggest changes. Whereas practice duration only weakly predicted individual differences in change, self-reported liking of the practices and degree of integration into daily life predicted changes on most scales. Interestingly, the magnitude of observed changes varied across scales. The strongest changes were observed for the regulatory aspects of IA, that is, how the body is used for self-regulation in daily life. No significant changes were observed for the Noticing aspect (becoming aware of bodily changes), which is the aspect that is predominantly assessed in other IA measures. This differential pattern underscores the importance to assess IA multi-dimensionally, particularly when interested in enhancement of IA through contemplative practice or other mind-body interventions.